Reconstruction of Restorative Justice Regulations Within the Indonesian Penal System Post-Law No. 1 of 2023 - Riyadi, Padlah (Pustaka Peradaban, 2024)
This study analyzes the integration of Restorative Justice principles within Indonesia's new Criminal Code (KUHP). The enactment of Indonesia's new Criminal Code (KUHP) represents a significant advancement in accommodating Restorative Justice principles. This approach prioritizes social harmony, offender rehabilitation, and victim rights as alternative resolutions. This normative legal study utilizes primary, secondary, and tertiary legal materials. The study finds that the new KUHP integrates Restorative Justice through provisions such as Article 51, which redefines the purpose of sentencing to emphasize offender education and rehabilitation aligned with ethical values, and Article 52, which reinforces the importance of human dignity. Furthermore, Article 132 supports extra-judicial resolutions by nullifying prosecutorial authority when such resolutions are achieved. Thus, the incorporation of Restorative Justice in the new KUHP lays a crucial foundation for a more equitable, inclusive, and humane criminal justice system.